Draft Annual Plan 1994-95 Vol. IV (In 4 Volumes) Haryana State - Planning Commission (Planning Commission, 1994)
The State Government is determined to achieve Universalization of Primary Education by the end of the current 8th Five year Plan. To achieve tins objective a number of special Programme and schemes have been launched. The main emphasis would be on enrolment, retention, qualitative improvement and Provision of infrastructural facilities. According to 1931 census, the projected, population in the 6-11 age group would be 2 ’15 lakhs by the end of 1996-97. In order to achieve Universalization, and taking into account the overage, underage children and drop outs, student enrolment equivalent to 120% the population in.6-11 age group will have to be achieved. Thus 24.13 lac children will have to be enrolled in primary classes by the end of the current 3th Five Year Plan 1996-97.
Government of Haryana
Planning Department Government of Haryana
Keywords: "Haryana state Annual Plan 1994-95; Technical Education; Sports; Ayurveda; Employees State Insurance; Housing including Police Housing; Haryana Institute of Public Administration; Women & Child Development; Employment Exchanges; Nehru Rozgar Yojna; Social Defence and Security; Industrial Training.